Rule based process selection of milling processes based on GD&T requirements - Sormaz, Dusan; Gouveia, Ronny; Sarkar, Arkopaul (Journal of Production Engineering, 2018)
The IMPlanner is an ongoing CAPP software project that enables rapid and detailed process selection of manufacturing processes based on specific details of CAD models such as GD&T requirements and feature recognition. A mapping of the different manufacturing routes possible for a given CAD design are outputted by the software, electing the optimal solution. Previously this software focused mainly on hole making operations however, further research has enabled its expansion towards milling operations.